Função e integridade renal de cães com diabetes mellitus - Silva, Andréa Cruvinel Rocha (2012)
Early diagnosis of diabetes mellitus (DM) in dogs or recognition of complications helps to increase the survival rate of animals. In human kidney complications caused by diabetes are well established, unlike canines. This study aimed to determine whether dogs with DM develop changes that lead to renal disease. We studied 31 diabetic dogs, which were divided into three groups, G1 realized that dogs without DR, G2, with urinary tract infection (UTI) and G3, with DR in stage 1. The evaluation consisted of history of animals, clinical examination, measurement of systolic arterial pressure (SAP) and laboratory tests: blood count, urinalysis, blood biochemistry (fibrinogen, glucose, urea, creatinine, total protein, albumin, globulin, phosphorus, calcium, sodium, potassium, fructosamine and cholesterol) and urine biochemistry (protein, creatinine, sodium, potassium and determined the activity of gama glutamiltransferase - GGT). Established the UPC and fractional excretion (EF) of sodium and potassium. The results show relation between DM and DR and the most relevant were found ITU and increase in the UPC, serum phosphorus, urinary GGT, cholesterol, fibrinogen and EF sodium and potassium. About the clinical signs observed polyuria, polydipsia, cataracts, polyphagia, weight loss, dehydration, and neoplasms. Dogs with a mean age of nine years, females, and the Poodle are more predisposed to diabetes. Dogs that have received specific diets, as well as laboratory monitoring, managed glycemic control and improved quality of life.